Perfectionism, burnout, and depression in youth soccer players: A longitudinal study - Smith, E. P.; Hill, A. P.; Hall, H. K. (Journal of Clinical Sport Psychology, 2018)
The relationship between perfectionism, burnout and depression among youth soccer players is of interest due to the competitive academy environments that must be navigated in order to become a professional soccer player. Three alternative theoretical models have been proposed to explain the relationship between perfectionism, burnout and depression. These models state that perfectionism is (a) a vulnerability factor for burnout and depression (vulnerability model), (b) a consequence of burnout and depression (complication/scar model), or (c) that the relationships are reciprocal (reciprocal relations model). The purpose of this study was to test these three models in youth soccer players. One hundred and eight male soccer players (M=16.15 years, SD=1.84) from professional clubs completed measures of perfectionism, burnout symptoms, and depressive symptoms twice, three months apart. Cross-lagged panel analysis provided support for a reciprocal relations model for burnout symptoms and a complication/scar model for depressive symptoms.